Comparative study of two modes of gastroesophageal reflux measuring: conventional esophageal pH monitoring and wireless pH monitoring - Azzam,Rimon Sobhi (2012)
CONTEXT: Esophageal pH monitoring is considered to be the gold standard for the diagnosis of gastroesophageal acid reflux. However, this method is very troublesome and considerably limits the patient's routine activities. Wireless pH monitoring was developed to avoid these restrictions. OBJECTIVE: To compare the first 24 hours of the conventional and wireless pH monitoring, positioned 3 cm above the lower esophageal sphincter, in relation to: the occurrence of relevant technical failures, the ability to detect reflux and the ability to correlate the clinical symptoms to reflux. METHODS: Twenty-five patients referred for esophageal pH monitoring and with typical symptoms of gastroesophageal reflux disease were studied prospectively, underwent clinical interview, endoscopy, esophageal manometry and were submitted, with a simultaneous initial period, to 24-hour catheter pH monitoring and 48-hour wireless pH monitoring. RESULTS: Early capsule detachment occurred in one (4%) case and there were no technical failures with the catheter pH monitoring (P = 0.463). Percentages of reflux time (total, upright and supine) were higher with the wireless pH monitoring (P < 0.05). Pathological gastroesophageal reflux occurred in 16 (64%) patients submitted to catheter and in 19 (76%) to the capsule (P = 0.355). The symptom index was positive in 12 (48%) patients with catheter pH monitoring and in 13 (52%) with wireless pH monitoring (P = 0.777). CONCLUSIONS: 1) No significant differences were reported between the two methods of pH monitoring (capsule vs catheter), in regard to relevant technical failures; 2) Wireless pH monitoring detected higher percentages of reflux time than the conventional pH-metry; 3) The two methods of pH monitoring were comparable in diagnosis of pathological gastroesophageal reflux and comparable in correlating the clinical symptoms with the gastroesophageal reflux.